Aspects of How Teachers and Students Use Instructional Materials for Effective Instructional and Learning of History. - Chimpaye, Edith (Kabale University, 2024)
The study focused on how teachers and students utilize instructional materials to enhance the teaching and learning of history, aiming to investigate their effectiveness and the challenges faced in secondary schools in Kisoro Municipality. The objectives included examining the impact of instructional materials on students' performance in history, identifying challenges faced by teachers and students in using these materials, and proposing solutions to these challenges. The research covered the background, problem statement, purpose, objectives, research questions, scope, and significance of the study. A literature review was conducted, analyzing related research by various authors to help draw conclusions. Data collection methods included questionnaires and interviews. The study concluded that while instructional materials are essential for effective teaching, they cannot replace quality teaching strategies. These materials should be used to supplement, not replace, skilled instruction. Students often perform poorly without teaching aids, but they need a competent teacher to achieve their best results. The study recommended that the Ugandan government, through the Ministry of Education, should address the challenges hindering the teaching and learning of history, ensure schools have adequate teaching materials, and train teachers on how to improvise when materials are unavailable in most secondary schools in Kisoro Municipality, Kisoro District.